VACANT HOUSE TAX, A SOLUTION TO HIGH HOUSE PRICES - Dinata, I Putu Hendy Bimantara; Tandioga, Frenly Allen Samuel; Cendekiawan, Muslim; Suci, Saraswati Nirmala (Polytechnic of State Finance STAN, 2024)
This paper will discuss the proposed Vacant House Tax (VHT) implementation scheme in Indonesia, the benefits and potential of VHT implementation in Indonesia, as well as the challenges that must be faced by the government in implementing this tax in Indonesia. the research uses a qualitative method in discussing the topic that is the purpose of this research. The qualitative method in this research is conducted by collecting various literature from books, articles, news, and so on that are relevant to the topic discussed. The potential for additional revenue from VHT is significant enough to increase Regional Original Revenue. This research also provides an overview of the challenges that may occur in the implementation of VHT such as: determining the status and ownership of vacant houses, regulatory adjustments, and environmental and monetary impact. there are research limitations such as in calculating the potential that uses several assumptions caused by the absence of data on the number of vacant houses in Indonesia so that it uses estimated data according to the OECD. This research can add to the study of taxation literature in Indonesia. The research can also be a consideration for the government in designing a tax imposition scheme on vacant houses.